2021
DOI: 10.1002/slct.202100674
|View full text |Cite
|
Sign up to set email alerts
|

Review on Colloidal Quantum Dots Luminescent Solar Concentrators

Abstract: Luminescent solar concentrators (LSCs) have recently gained popularity as an effective solution to increase solar energy conversion. Utilizing LSCs together with solar cells can generate more energy at a lower cost than using only solar cells. LSCs operate by utilizing luminophores, molecules that absorb incident solar irradiation and re‐emit photons, and waveguides that redirect emitted photons to the edges of a glass or polymer slab at high concentrations. Many quantum dots (QDs) have been the focus of much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 184 publications
0
22
0
Order By: Relevance
“…12 }-Y@PVP Films PVP is the second example of matrixes used in these works, and it is often a good candidate complementary to the SiO 2 -PEG matrix. Indeed, the PVP is a nontoxic, biodegradable and biocompatible polymer with an interesting temperature resistance and pH stability, recently used for energy and optical applications [11,12,14,30,32,33,[39][40][41][42][43][44][45][46][47]. These results, especially thus on thin films, have shown that it is clearly possible to incorporate inorganic nanoparticles or nanoclusters directly at high concentrations into a PVP matrix without observing any segregation between the organic and inorganic phases.…”
Section: Study Of the {Nb 6-x Ta X X Imentioning
confidence: 99%
“…12 }-Y@PVP Films PVP is the second example of matrixes used in these works, and it is often a good candidate complementary to the SiO 2 -PEG matrix. Indeed, the PVP is a nontoxic, biodegradable and biocompatible polymer with an interesting temperature resistance and pH stability, recently used for energy and optical applications [11,12,14,30,32,33,[39][40][41][42][43][44][45][46][47]. These results, especially thus on thin films, have shown that it is clearly possible to incorporate inorganic nanoparticles or nanoclusters directly at high concentrations into a PVP matrix without observing any segregation between the organic and inorganic phases.…”
Section: Study Of the {Nb 6-x Ta X X Imentioning
confidence: 99%
“…By contrast, quantum dots and quantum rods have been intensively studied for applications such as LCDs, 25 micro-LED displays, 26 and LSCs. 27 Their narrow emission spectra result in a larger color gamut for display applications. Large Stroke's shift mitigates the photon loss due to selfabsorption in LSCs.…”
Section: Future Developmentmentioning
confidence: 99%
“… 42 46 QDs exhibit a narrow, tunable, and symmetric emission spectrum compared to organic fluorophores. 47 , 48 However, QDs with small capping agents tend to aggregate or agglomerate. Thus, large molecules such as biopolymers can be used as stabilizers and capping agents for QDs.…”
Section: Introductionmentioning
confidence: 99%